2018
DOI: 10.1002/elps.201800305
|View full text |Cite
|
Sign up to set email alerts
|

Searching for biomarkers of chronic obstructive pulmonary disease using proteomics: The current state

Abstract: Detection of proteins which may be potential biomarkers of disorders represents a big step forward in understanding the molecular mechanisms that underlie pathological processes. In this context proteomics plays the important role of opening a path for the identification of molecular signatures that can potentially assist in early diagnosis of several clinical disturbances. Aim of this report is to provide an overview of the wide variety of proteomic strategies that have been applied to the investigation of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Among these, proteomics is a powerful and promising tool for detecting novel prognostic proteins that has been extensively used for disease biomarker discovery [35] . Recently, an increasing number of studies have utilized proteomics for COPD biomarker discovery [36–39] . However, to our knowledge, this technique has not been applied to examine the serum biomarkers in smokers with and without COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, proteomics is a powerful and promising tool for detecting novel prognostic proteins that has been extensively used for disease biomarker discovery [35] . Recently, an increasing number of studies have utilized proteomics for COPD biomarker discovery [36–39] . However, to our knowledge, this technique has not been applied to examine the serum biomarkers in smokers with and without COPD.…”
Section: Discussionmentioning
confidence: 99%
“… [35] Recently, an increasing number of studies have utilized proteomics for COPD biomarker discovery. 36 37 38 39 However, to our knowledge, this technique has not been applied to examine the serum biomarkers in smokers with and without COPD. Thus, we performed an iTRAQ-based proteomic analysis to identify the serum biomarkers in smoker patients with COPD and normal smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cells release some of their contents into the blood at the time of damage or death, which makes serum/plasma one of the most important sources of information for COPD proteomics. 26 Pratte et al 45 confirmed that soluble receptor for advanced glycation end products (sRAGE) is a prognostic biomarker for COPD by analyzing plasma sRAGE levels in four independent cohorts and found that lower plasma sRAGE levels associated with reduced forced expiratory volume in the first second (FEV1) and exacerbation of emphysema. Plasma sRAGE is a predictor of emphysema progression, and it is also the most promising blood COPD biomarker.…”
Section: Serum/plasmamentioning
confidence: 97%
“… 24 , 25 In addition, proteomics has the potential to reveal some disease mechanisms that cannot be identified at the genetic level. 26 Meanwhile, most types of specimens in proteomic studies can be easily collected in a less invasive and reproducible way. Because of these advantages, proteomic approaches have been used in many chronic lung diseases, including COPD, idiopathic pulmonary fibrosis (IPF), 27 pulmonary sarcoidosis, 28 asthma, 29 etc.…”
Section: Proteomics Of Copdmentioning
confidence: 99%
“…Proteomics aims to identify potential protein biomarkers of diseases and has become a hot tool in basic research and clinical research, which can indeed reveal meaningful patterns and produce credible views on complex biological systems. In addition, proteomics has the potential to reveal some disease mechanisms that cannot be determined at the genomic level and has great advantages for direct clinical relevance [22]. Due to these advantages, proteomics methods have been used in many chronic lung diseases, such as cystic fibrosis [23], idiopathic pulmonary fibrosis (IPF) [24], sarcoidosis [25], asthma [26], etc.…”
Section: Proteomics Of Copdmentioning
confidence: 99%